2018
DOI: 10.1590/0100-29452018794
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, anti-Trypanosoma cruzi and cytotoxic activities of the essential oil from green fruits of Protium ovatum (BURSERACEAE)

Abstract: -Chagas disease is a major neglected tropical disease caused by Trypanosoma cruzi. It has been treated with the antiparasitic drugs nifurtimox and benzonidazole, which cause several side effects. The market for natural products has considerably grown lately and the use of plants has become an alternative to the development of novel drugs to cure the disease. Therefore, this study aimed at describing the chemical analysis of the essential oil from green fruits of Protium ovatum and evaluating their trypanocidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
2
8
0
2
Order By: Relevance
“…( E )‐caryophyllene was one of the major compounds in the species considered promising active, corroborating with previous anti‐ T. cruzi activitites studies involving ( E )‐caryophyllene rich EOs such as Cordia verbenaceae (18.77 %), Eugenia brejoensis (9.77 %), Hyptis pectinata (30.91 %), Annona pickelii (27.8 %), Protium ovatum (14 %), and Vernonia brasiliana (10.4 %) [21–25] …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…( E )‐caryophyllene was one of the major compounds in the species considered promising active, corroborating with previous anti‐ T. cruzi activitites studies involving ( E )‐caryophyllene rich EOs such as Cordia verbenaceae (18.77 %), Eugenia brejoensis (9.77 %), Hyptis pectinata (30.91 %), Annona pickelii (27.8 %), Protium ovatum (14 %), and Vernonia brasiliana (10.4 %) [21–25] …”
Section: Resultssupporting
confidence: 86%
“…It is interesting to observe that among the identified compounds in E. florida EOs, a significant trypanocidal activity can be attributed to the presence of α‐pinene and ( E )‐caryophyllene, since both compounds displayed anti‐ T. cruzi activity in previous studies [17,21–25] . There are also reports of improved anti‐ T. cruzi activity achieved by the combination of limonene and caryophyllene oxide [26,27] …”
Section: Resultsmentioning
confidence: 92%
“…Studies carried out by this research group have aimed at analysing the chemical composition and biological activities of essential oils (Estevam et al, 2017;Estevam et al, 2018), and this one, specifically, addresses the chemical composition and the in vitro antifungal activity of M. paniculata (Figure 1) against S. sclerotiorum.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies carried out by the members of this research group reported the content and the chemical composition of essential oils extracted from C. adamantium and C. calophyllum leaves and from P. ovatum leaves and green fruits. Mean contents of essential oils found after hydrodistillation of C. adamantium and C. calophyllum leaves and of P. ovatum leaves and green fruits were 0.32%, 0.06%, 0.30% and 0.50%, respectively (Oliveira et al, 2017;Xavier et al, 2016b;Estevam et al, 2017;Estevam et al, 2018).…”
Section: Resultsmentioning
confidence: 94%
“…Major constituents identified in essential oils from C. adamantium leaves were spathulenol (19.27%), germacrene-B (18.27%) and β-caryophyllene oxide (12.37%) (Oliveira et al, 2017), whereas, in the ones from P. ovatum leaves, they were spathulenol (17.60%), β-caryophyllene (14.00%) and β-myrcene (8.40%) (Estevam et al, 2017). Major constituents of essential oils from P. ovatum green fruits were and β-myrcene (62.0%), α-pinene (11.3%) and limonene (7.3%) (Estevam et al, 2018), while C. calophyllum leaves displayed spathulenol (28.78%), viridiflorol (9.99%) and (Z,E)-pharnesol (6.51%) (Xavier et al, 2016b).…”
Section: Resultsmentioning
confidence: 98%